Challenging the Prison-Industrial Complex : Activism, Arts, and Educational Alternatives - Hartnett, Stephen J. (Book collections on Project MUSE., 2011)
Stephen John Hartnett is an associate professor and chair of communication at the University of Colorado Denver. He is the author of Incarceration Nation: Investigative Prison Poems of Hope and Terror and Executing Democracy, Volume One: Capital Punishment and the Making of America, 1683-1807. --Book Jacket.